ANALISIS ENERGI DAN PROTEIN SERTA UJI DAYA TERIMA BISKUIT TEPUNG LABU KUNING DAN IKAN LELE - IKA ROHIMAH; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Diversification program needs no introduction processed pumpkin and catfish to get new food alternatives . Yellow squash and catfish have the potential as a source of nutrients because it contains a number of macro-nutrients and micro-nutrients. The purpose of this study was to determine the nutrient content of energy and protein biscuits and test the acceptance of pumpkin flour and catfish organoleptic analysis covering the taste, aroma, color, and texture of the biscuit is determined by using a hedonic scale.This study is an experimental research making biscuits with the addition of pumpkin flour and catfish by 20 %, 30 %, and 40 %. Meanwhile, the protein content using the method Kjeldhal, fat extraction method, carbohydrate hydrolysis method, and energy by using the method of calculations carried out in the laboratory of Research and Standardization Agency for Industrial Field. Panelists in this study was the son of SD Negeri No. 067 097 Medan, as many as 30 people, FKM USU students as much as 30 people, and pregnant women at the Maternity Clinic as many as 30 people. The results showed that pumpkin flour biscuits and catfish has an energy content of 40% and a high protein and low in carbohydrates and fat. Based on the results of organoleptic test showed that the addition of flour biscuits with pumpkin and catfish include aroma, color, flavor, and texture are the most preferred and pumpkin flour biscuits catfish 20 % in primary school children. Advised the public to be able to make biscuits and pumpkin flour catfish as a food supplement for pregnant women and for children of primary school age and developmental growth. Also, further research needs to be done on making pumpkin flour biscuits and catfish to enhance the flavor and aroma that pregnant women like to eat pumpkin biscuit flour and catfish. Keywords :   Analysis, Energi and Protein, Biscuits, Pumpkin Flour Yellow, Catfish Meal, Power Accept